ACCOUNTING FOR LEASEHOLDS. - Bogart, Fred O. (The Accounting Review, 1950)
Abstract This paper is written in criticism of the usual textbook treatment of the amortization of prepaid leaseholds. The usual treatment violates theory in atleast three aspects: (1) It violates the accounting convention by recording book interest on costs incurred. (2) It mismatches costs with revenue. (3) It results in an improper valuation of the prepaid lease for balance sheet purposes. The accounting convention that no interest should be considered earned and recorded as such on the equipment would seem to apply to the prepaid lease as well. The amount of any cost incurred is, fundamentally, the present value of future service. It is sometimes argued that since interest was a consideration in determining the amount to be prepaid, that interest should therefore be considered earned and recorded on the prepayment. It is also true that interest is or should be a consideration in the determination whether one should purchase or lease. It is further true that interest is a consideration in the determination of whether one should engage his money in a business. But, after the determination is made and the cost incurred for assets of a business, it does not follow that interest should be a consideration to be recorded in the books of account.